2001
DOI: 10.1002/ijc.1642
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between a single nucleotide polymorphism in the alcohol dehydrogenase 3 gene, alcohol consumption and oral cancer risk

Abstract: We investigated effects on oral cancer (OC) risk of an interaction between a single nucleotide polymorphism (SNP) in the alcohol dehydrogenase 3 (ADH 3 ) gene and alcohol consumption levels using a hospital-based study of 93 cases and 99 controls conducted in Athens, Greece. This SNP affects ethanol metabolism in vitro and appeared to interact with alcohol consumption in a previous OC study. We also evaluated a SNP in CYP2E1, another gene involved in ethanol metabolism, reported to be associated with OC risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
2
26
2
1
Order By: Relevance
“…However, our data did not show the risk of HNSCC to be significantly associated with the genotypes of ADH3 after adjusting for age, race, tobacco, and alcohol usage. This lack of association with ADH3 genotypes was also noted by other investigators (6,7,14,15). Our results were in contrast with two other reports which showed that participants with the ADH3 1-1 genotype had a much higher risk of head and neck cancer (5,13), and another study showing that participants with ADH3 1-1 had borderline higher risk for oral cancer only (17).…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…However, our data did not show the risk of HNSCC to be significantly associated with the genotypes of ADH3 after adjusting for age, race, tobacco, and alcohol usage. This lack of association with ADH3 genotypes was also noted by other investigators (6,7,14,15). Our results were in contrast with two other reports which showed that participants with the ADH3 1-1 genotype had a much higher risk of head and neck cancer (5,13), and another study showing that participants with ADH3 1-1 had borderline higher risk for oral cancer only (17).…”
Section: Discussioncontrasting
confidence: 88%
“…Second, sample size is an important issue in genetic studies. Interestingly, the sample sizes for the two studies showing that ADH3 1-1 had significantly increased risk of head and neck cancer were much smaller than the ones that did not find the association (5)(6)(7)(13)(14)(15). In addition, the controls of these two studies were either alcoholics or heavy drinker (z57drinks per week).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…58 Elevated odds (OR 5.3, 95% CI, 1.0-28.8) of oral cancer in association with the ADH1C*1-1 genotype were observed only among heavy alcohol users (57 drinks per week) in Puerto Rico 59 and among alcoholics in Germany 60 and France. 55,61 However, contradictory conclusions were reported in studies conducted in the U.S. 62,63 and Greece, 64 in which the ''slow metabolizing'' ADH1C*2-2 genotype was associated with increased risk for HNSCC among heavy drinkers. Other studies reported no associations between ADH genotype and risk of HNSCC.…”
Section: Alcohol Consumption and Metabolismmentioning
confidence: 99%